Hierarchical Modelling of ESG Risk and Firm Value: A Mediation–Moderation Analysis - Saputro, Tri Hijrah; Ichwanudin, Wawan; Hanifah, Imam Abu (Jurnal Bisnis Mahasiswa, 2025)
This study examines the effect of ESG Risk Rating on firm value using a hierarchical modelling approach. The research addresses inconsistent findings in emerging markets by analyzing direct, indirect, and conditional effects. Based on balanced panel data from 13 non-financial firms listed in IDX ESG Leaders during 2020–2023, three models are tested: a baseline model, a mediation model with asset efficiency (TATO), and a moderated mediation model with profitability (ROA). The results show that ESG Risk does not have a direct significant effect on firm value, but it does have a negative indirect effect through TATO. Profitability significantly moderates the relationship between TATO and firm value, but not between ESG Risk and TATO. The moderated mediation effect is only significant at low levels of profitability. These findings suggest that ESG efforts alone do not enhance firm value unless combined with operational efficiency and financial strength. This study offers insights for firms and policymakers to align ESG practices with internal performance, thereby creating sustainable value in emerging markets.